Electrolyzer array alternate control strategy considering wind power prediction. (November 2022) - Zhao, Yuyang; Zhu, Zhengzheng; Tang, Sihang; Guo, Yingjun; Sun, Hexu
Abstract: Non grid connected wind power hydrogen production technology is of great significance for the large-scale comprehensive utilization of hydrogen energy and accelerating the development of clean energy. In this paper, an electrolyzer power allocation and alternate control method for non grid connected wind power hydrogen production is proposed, and the optimized control strategy are combined to predict the maximum wind power of certain time interval. While retaining the required data characteristics, the instantaneous fluctuation of some wind power data is eliminated, which provides a reliable basis for power distribution in the alternation control strategy of electrolyzer array. The case simulation verifies the effectiveness of the electrolyzer array control principle and the prediction of the maximum wind power. While ensuring the absorption effect and hydrogen production rate, the service life and operation safety of the electrolyzer array are effectively improved by balancing the working state of each electrolyzer.